Brine Shrimp Lethality Test (BSLT) Ekstrak Sarang Lebah Madu (Apis dorsata Binghami - Yermia Semuel Mokosuli (Jurnal Pendidikan Biologi undiksha, 2021)
Apis dorsata Binghami is a honey bee endemic to the Walacea Zone. Apis dorsata Binghami that has not been bred has a higher variety of feed sources than other honey bees. Apis dorsata Binghami's nest is made of different types of nectar, propolis and pollen than Apis mellifera. Research has been carried out to determine the toxicity of Apis dorsata Binghami honeycomb extract based on the BSLT (Brine Shrimp Lethality Test) test. Fresh Apis dorsata nests were obtained from the Minahasa forest, North Sulawesi. After being air-dried, the honeycomb was extracted using the maceration method with a ratio of 1:2 (w/v) simplicia nest and solvent. Ethanol extracts were examined for their toxicities to shrimp larvae Artemia salina Leach. The test concentrations used were 10 mg/L, 100 mg/L, 500 mg/L and 1000 mg/L. Each concentration was carried out in three replications. The results showed that the LC50 of the honeycomb ethanol extract was LC50 54,457 mg/L. Based on the LC50, the honeycomb of Apis dorsata Binghami can be consumed directly by humans and contains bioactives that have medicinal potential.